A rare presentation of hypovolemic shock secondary to Whipple's disease. Issue 5 (May 2019) - Tandon, Parul; Huang, Vivian; Jaffer, Nasir; Kirsch, Richard; Croitoru, Kenneth
Abstract : Whipple's disease is a rare, multisystem infection caused by the Gram-positive Tropheryma whippelii organism. In addition to neurological and rheumatological manifestations, this disease can result in significant gastrointestinal symptoms such as malabsorption, diarrhea, and weight loss. Given the diagnostic challenge and rare occurrence, a high index of suspicion is critical to prevent morbidity and mortality from this otherwise highly infectious disease transmitted via the fecal-oral route. We present a very rare but near-fatal case of hypovolemic shock secondary to protein-losing enteropathy and gastrointestinal bleeding from small bowel T. whippelii infection. Furthermore, the epidemiology, clinical presentation, diagnosis, and management of Whipple's disease is reviewed.